Regular consumption of fresh orange juice increases human skin carotenoid content. (18th August 2015) - Massenti, Roberto; Perrone, Anna; Livrea, Maria Antonietta; Lo Bianco, Riccardo
Abstract: Dermal carotenoids are a good indicator of antioxidant status in the body. This study aimed to determine whether regular consumption of orange juice could increase dermal carotenoids. Two types of orange juice, obtained from regularly (CI) and partially (PRD) irrigated trees, were tested to reveal any possible association between juice and dermal carotenoids. Soluble solids, titratable acidity, and total carotenoids were quantified in the juice; skin carotenoid score (SCS) was assessed by Raman spectroscopy. Carotenoid content was 7.3% higher in PRD than in CI juice, inducing no difference in SCS. In a first trial with daily juice intakes for 25 days, SCS increased linearly (10%) in the individual with higher initial SCS, and exponentially (15%) in the individual with lower initial SCS. In a second trial, SCS showed a 6.5% increase after 18 days of drinking juice every other day, but returned to initial values three days after last intake. Skin carotenoids can be increased by regular consumption of fresh orange juice, while their persistence may depend on the accumulation level, environmental conditions or living habits.